Teachers Experiences in Using Technology Integration in English Language Teaching - Archie Elmassetyo Hartono; Pasca Kalisa; Nahdiyah Hidayah (English Teaching Journal : A Journal of English Literature, Language and Education, 2025)
This study examines how English language teachers working in ELT institutions approach technology integration as part of their instructional practices and overall teacher experiences with digital tools. Using a qualitative research design, the researcher conducted semi-structured interviews with seven educators to explore the perceived benefits, constraints, and strategies related to technology use in English language teaching. The findings show that technology can strengthen student engagement, foster creativity, and support collaborative learning, although its effective implementation is limited by issues such as insufficient infrastructure, uneven digital literacy, and time constraints. The study highlights the importance of institutional support, particularly improved technological resources, targeted training, and ongoing professional development, to help teachers integrate technology with greater confidence and purpose.